Quantum Random Walk - Atakol, Mehmet (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
We present an in-depth analysis of the "quantum first detection problem," in other words, quantum renewal equation (QRE) [1] and how it relates to the basic postulates of quantum existence in this thesis. It shows how the Schrödinger equation and projective measurement postulate a guide to the solution of the problem and present equations that describe the system’s behavior. The text highlights the surprising features of the problem for closed systems and the sensitivity of the problem to the sampling rate. It also notes that the probability of being eventually detected can be less than unity for finite-sized systems.

ÖZ: Bu tez, kuantum ilk saptama probleminin (kuantum yenileme denklemi) derinlemesine bir analizini ve bunun kuantum gerçekliginin temel varsayımlarıyla ˘ nasıl bir ili¸skisi oldugunu sunar. Schrödinger denklemi ve izdü¸sümsel ölçüm ˘ varsayımının sorunun çözümüne nasıl yol açtıgını ve sistemin davranı¸sını tanımlayan ˘ denklemleri nasıl sundugunu gösterir. Kapalı sistemler için problemin ¸sa¸sırtıcı ˘ özelliklerini ve problemin ölçüm hızına olan hassasiyetini vurgulamaktadır. Ayrıca, nihai olarak tespit edilme olasılıgının, belirli boyutta sistemler için birim sayıdan daha ˘ az olabilecegini de not eder.
Master of Science in Physics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2023. Supervisor: Assist. Prof. Dr. Mustafa Rıza.
Keywords: Thesis Tez; Physics Department; Quantum Mechanics; Quantum Physics; Quantum Theory; Energy--Quantum Mechanics; Quantum Renewal Equation; Schrödinger Equation; Quantum Postulates